How does an interactive approach to literary texts work in an English as a foreign language context? Learners' perspectives in close-up. Issue 3 (1st September 2016) - Nguyen, Ha Thi Thu
Abstract : Interactive approaches to literary texts in second/foreign language education have enjoyed wide theoretical and empirical support. However, the teaching of literary texts in traditional English as a foreign language contexts still remains information-oriented, with a focus on the transmission and replication of an objectified interpretation of a text. This paper examines the working of a project that implemented an interactive approach based on a combination of reader-response theory and social-constructivist theory to teaching English literary texts in Vietnam, focusing on the students' perspectives of their learning experience. The findings show that the project pedagogy not only helped the students become more active, dialogic and reflective in constructing the interpretations of the texts they studied, but also subjected the students to the tensions of creating a new learning paradigm in a traditional context. Negotiation of these tensions, however, enabled strategic and critical learning to happen.